2002
DOI: 10.1007/s00268-001-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Current value of intraoperative sonography during surgery for hepatic neoplasms

Abstract: Noninvasive liver imaging has developed rapidly resulting in increased accuracy for detecting primary and secondary hepatic tumors. Intraoperative ultrasonography (IOUS) was commonly considered to be the gold standard for liver staging, but the current value of IOUS is unknown in view of more sophisticated radiologic tools. The purpose of this prospective study was to evaluate the impact of IOUS on the treatment of 149 patients undergoing liver surgery for malignant disease (colorectal metastasis, 61 patients;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 28 publications
4
97
0
6
Order By: Relevance
“…It allows for a very good characterization of focal liver lesions, with both sensitivity and specificity values over 90% [10][11][12][13][14]. Of the 73 patients included in the study in 41 (56.2%) patients the focal liver lesions found at IOUS were classified as malignant and in 32 (43.8%) patients the focal liver lesions found at IOUS were classified as benign.…”
Section: Discussionmentioning
confidence: 99%
“…It allows for a very good characterization of focal liver lesions, with both sensitivity and specificity values over 90% [10][11][12][13][14]. Of the 73 patients included in the study in 41 (56.2%) patients the focal liver lesions found at IOUS were classified as malignant and in 32 (43.8%) patients the focal liver lesions found at IOUS were classified as benign.…”
Section: Discussionmentioning
confidence: 99%
“…5,16 In addition, MRI has particular shortcomings that may contraindicate its use, such as the presence of metal prostheses and claustrophobia. 3,10 This may explain reports that IOUS detects lesions in up to 40% of patients not detected by PoI and alters surgical strategy in 25.7% of patients undergoing resection for CRlM. 5,16 The role of IoUS may be more important as laparoscopic liver surgery becomes more frequent due to the absence of intraoperative digital palpation.…”
Section: Discussionmentioning
confidence: 95%
“…3,[9][10][11][12] However, some earlier studies reported a limited clinical value of IoUS. 13,14 Regarding detection of liver lesions, PoI alone attains a sensitivity of 41-68% with transabdominal ultrasound, 60-75% with contrastenhanced CT and 80-85% with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC) IOUS allows detection of new lesions in 7% of cases at the primary hepatectomy and in 7.3% at the secondary hepatectomy [2]. In an analysis related to patients with colorectal liver metastases (CLM), sensitivity of computed tomography (CT) was 69.2%, of helical CT 82.5%, of magnetic resonance imaging (MRI) 84.9%, and of IOUS 95.2% [3]. CT and MRI cannot substitute the real time information provided by IOUS.…”
Section: Introductionmentioning
confidence: 99%